Cinnamaldehyde ameliorates LPS-induced cardiac dysfunction via TLR4-NOX4 pathway: The regulation of autophagy and ROS production. (December 2016) - Zhao, Hang; Zhang, Meng; Zhou, Fuxing; Cao, Wei; Bi, Linlin; Xie, Yanhua; Yang, Qian; Wang, Siwang
Abstract: Cinnamaldehyde (CA), a major bioactive compound extracted from the essential oil of Cortex Cinnamomi, exhibits anti-inflammatory activity on endotoxemia. Accumulating evidence indicates reactive oxygen species (ROS) and autophagy play a vital role in the cardiac dysfunction during endotoxemia. The aim of this study was to unveil the mechanism of CA on ROS production and autophagy during endotoxemia. Male Sprague-Dawley rats were stimulated by LPS (20 mg/kg i.v.) with or without treatment of CA. Cardiac function and histopathological staining were preformed 4 h after LPS stimulation. The levels of TNF-α, IL-1β and IL-6 were detected by ELISA. The expression of p-JNK, p-ERK, p-p38, TLR4, NOX4, NOX2, ATG5 and LC3 proteins were determined by Western blot. The results showed that CA inhibited cardiac dysfunction, inflammatory infiltration and the levels of TNF-α, IL-1β and IL-6 in LPS stimulated rats by blocking the TLR4, NOX4, MAPK and autophagy signalings. In order to obtain further confirmation of the mechanism of CA on endotoxemia in vitro, a limited time-course study was firstly performed by Western blot. TLR4, NOX4 and LC3 were significantly increased after 4 h LPS stimulation. CA reversed the intracellular ROS production and MAPK signaling activation induced by LPS. Electron microscopy, mRFP-GFP-LC3 transfection and western blot results revealed autophagic flux were attenuated after CA treatment. The siRNA and molecular docking results suggest that CA can suppress both TLR4 and NOX4 during endotoxemia. Our data revealed that CA ameliorated LPS-induced cardiac dysfunction by inhibiting ROS production and autophagy through TLR4-NOX4 pathway. Graphical abstract: Highlights: CA attenuate ROS production and autophagy which result in cardiac protection and cell survival. NOX4 but not NOX2 was significantly enhanced after LPS stimulation and suppressed by CA. CA exhibit anti-inflammation activity by directly suppress TLR4 and NOX4. Homology modeling and molecular docking was used to imitate the conjunction of CA with both TLR4 and NOX4.